2022
DOI: 10.3389/fcell.2022.994037
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the interplay between autophagy and oxidative and endoplasmic reticulum stress in neuronal cell death and survival

Abstract: Autophagy is a dynamic process that maintains the normal homeostasis of cells by digesting and degrading aging proteins and damaged organelles. The effect of autophagy on neural tissue is still a matter of debate. Some authors suggest that autophagy has a protective effect on nerve cells, whereas others suggest that autophagy also induces the death of nerve cells and aggravates nerve injury. In mammals, oxidative stress, autophagy and endoplasmic reticulum stress (ERS) constitute important defense mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 256 publications
(180 reference statements)
0
7
0
Order By: Relevance
“…A great number of studies suggested that overproduction of ROS was also closely associated with ERS . In addition, there was extensive cross-talk between autophagy and ERS and the deficiency of autophagy flux could stimulate ERS activation and augment ERS-induced cell injury. , Therefore, the effect of F10 on ER deserves further analysis. The phosphorylation of eIF2α at Ser10 is essential for the ERS response; in addition, studies strongly support the view that phosphorylation of eIF2α is a specific marker of ICD .…”
Section: Resultsmentioning
confidence: 99%
“…A great number of studies suggested that overproduction of ROS was also closely associated with ERS . In addition, there was extensive cross-talk between autophagy and ERS and the deficiency of autophagy flux could stimulate ERS activation and augment ERS-induced cell injury. , Therefore, the effect of F10 on ER deserves further analysis. The phosphorylation of eIF2α at Ser10 is essential for the ERS response; in addition, studies strongly support the view that phosphorylation of eIF2α is a specific marker of ICD .…”
Section: Resultsmentioning
confidence: 99%
“…During the process of lysosome-dependent autophagy, damaged organelles, aggregated proteins, and degraded cytoplasmic debris accumulate within autophagic vacuoles ( Gao et al ., 2022 ; Zhang et al ., 2022 ). Autophagy has been recognized to play roles in the regulatory and developmental phases of lung damage.…”
Section: Discussionmentioning
confidence: 99%
“…PM obstructs the mammalian target of rapamycin (mTOR), a cellular nutritional status sensor, and intensifies cellular oxidative stress, culminating in cellular apoptosis and autophagy, causing the breakdown of cellular components ( Yan et al ., 2021 ). Autophagy, a crucial lysosome-dependent mechanism that contributes to cellular homeostasis, has been connected to protein aggregation, organelle impairment, and the clearance of intracellular pathogens ( Gao et al ., 2022 ). Furthermore, autophagy’s implications in lung-related conditions underscore its significance in managing pulmonary disorders ( Zhang et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…EGCG is able to modulate autophagy in many cellular systems. Autophagy allows cells under oxidative stress to survive through its interaction with apoptosis and the MTOR-kinase AMP-activated alpha 1 catalytic subunit (PRKAA1/AMPK) [ 118 ]. It has been shown that EGCG promotes autophagy by forming autophagosomes and inducing lysosomal acidification and autophagic flow in Müller retinal cells.…”
Section: Epigallocatechin-3-gallatementioning
confidence: 99%